Typhoon: A Reliable Data Dissemination Protocol for Wireless Sensor Networks - Liang, Chieh-Jan Mike; Terzis, Andreas; Musăloiu-E., Răzvan (EWSN (European Conference on Wireless Sensor Networks), 2008)
We present Typhoon, a protocol designed to reliably deliver large objects to all the nodes of a wireless sensor network (WSN). Typhoon uses a combination of spatially-tuned timers, prompt retransmissions, and frequency diversity to reduce contention and promote spatial re-use. We evaluate the performance benefits these techniques provide through extensive simulations and experiments in an indoor testbed. Our results show that Typhoon is able to reduce dissemination time and energy consumption by up to three times compared to Deluge. These improvements are most prominent in sparse and lossy networks that represent real-life WSN deployments.